1997
DOI: 10.1091/mbc.8.6.1143
|View full text |Cite
|
Sign up to set email alerts
|

RCC1 and nuclear organization.

Abstract: We have examined the effect of RCC1 function on the nuclear organization of pre-mRNA splicing factors and poly(A)+ RNA in the tsBN2 cells, a RCC1 temperature-sensitive mutant cell line. We have found that at 4-6 h after shifting cells from the permissive temperature (32.5°C) to the restrictive temperature (39.5°C), both small nuclear ribonucleoprotein particles and a general splicing factor SC35 reorganized into 4-10 large round clusters in the nucleus, as compared with the typical speckled distribution seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…To verify that the cells have undergone the temperature shift, the localization of the trimethyl guanosine cap (TMG), a marker for the TMG-capped U snRNAs, was also examined. As previously reported, U snRNA localization shifts from widespread nucleoplasmic staining to less numerous foci when the RanGTP gradient is disrupted (Cheng et al, 1995;Huang et al, 1997). These data suggest that in contrast to previous reports (Cheng et al, 1995), the RanGTP gradient may not be required for localization of snoRNAs to the nucleolus.…”
Section: Mammalian Cellssupporting
confidence: 54%
See 1 more Smart Citation
“…To verify that the cells have undergone the temperature shift, the localization of the trimethyl guanosine cap (TMG), a marker for the TMG-capped U snRNAs, was also examined. As previously reported, U snRNA localization shifts from widespread nucleoplasmic staining to less numerous foci when the RanGTP gradient is disrupted (Cheng et al, 1995;Huang et al, 1997). These data suggest that in contrast to previous reports (Cheng et al, 1995), the RanGTP gradient may not be required for localization of snoRNAs to the nucleolus.…”
Section: Mammalian Cellssupporting
confidence: 54%
“…Previous work has shown that the temperature-sensitive RCC1 mutant, tsBN2, shows a change in the intra-nuclear localization of both small ribonucleoproteins (snRNPs) and the general splicing factor SC35 (Cheng et al, 1995;Huang et al, 1997) following a shift to the non-permissive temperature. Furthermore, biochemical experiments have implicated RCC1 in the transport of some but not all RNAs within the nucleus (Cheng et al, 1995).…”
mentioning
confidence: 99%
“…3B, merge) and L8057 (data not shown) cells. As controls, we also show colocalization of SCL and known partner Ldb-1, but not of an abundant unrelated nuclear protein (splicing factor SC35 [32]) with a component of the SCL complex such as Ldb-1 (Fig. 3B).…”
Section: In Vivo Biotinylation Of Sclmentioning
confidence: 69%
“…29) should similarly modulate the subnuclear localization of mammalian CDC5. In particular, tsBN2 cells (12) reorganize splicing factors into 4-10 large clusters at the restrictive temperature (13). To determine whether the CDC5 distribution is similarly reorganized, tsBN2 cells were shifted to 39.5°C for 10 h and costained for SC35 and CDC5.…”
Section: Resultsmentioning
confidence: 99%
“…TsBN2 cells (12) were cultured and shifted to the restrictive temperature for 10 h as described (13). Asynchronously growing subconfluent NIH 3T3 cells were rendered quiescent by incubation for 24 h in DMEM containing 0.1% bovine calf serum.…”
Section: Mammalian Cell Culture Conditions and Flow Cytometric Analysismentioning
confidence: 99%